Complex Regional Pain Syndrome, an Important Differential Diagnosis in Sports Injuries: a Case Report - Cabrera-Ubilla, Carlos; Cueto, Germán; Lucas, Christian (International Journal of Medical Students, 2024)
Background: Complex regional pain syndrome (CRPS) is a disproportionate and persistent, regional pain related to a minor trauma. Although CRPS is not an infrequent condition its pathophysiology remains unknown and leading to underdiagnosis or late diagnosis. The diagnosis is clinical, according to Budapest criteria of the International Association for the Study of Pain. Bone scintigram is the most effective test to support the diagnosis. The aim of this article is to discuss the importance of clinical suspicion for an early CRPS diagnosis in a sprain’s young athlete clinical case. The Case: We present the case of a sixteen-year-old male patient with no medical history who suffered two minor ankle injuries in the right foot. The patient developed severe and persistent pain associated with vasomotor, sudomotor and trophic abnormalities. He remained undiagnosed for 10 months until CRPS diagnosis confirmation supported by a bone scintigram. He received multiple treatments until spontaneous remission in the fourth year of evolution. Discussion: CRPS poses a diagnostic challenge that requires early suspicion to improve treatment outcomes and prognosis. Maintaining a high index of clinical suspicion is crucial, and CRPS should be considered in the evaluation of any persistent pain sport-related injury. Despite extensive research on CRPS conducted in recent decades, this condition may still be unfamiliar to many healthcare providers. Increasing awareness of CRPS among medical professionals can facilitate timely and accurate diagnosis, which is essential for effective management.